The Pediatrics Milestones Assessment Pilot: Development of Workplace-Based Assessment Content, Instruments, and Processes. (May 2016) - Hicks, Patricia J.; Margolis, Melissa; Poynter, Sue E.; Chaffinch, Christa; Tenney-Soeiro, Rebecca; Turner, Teri L.; Waggoner-Fountain, Linda; Lockridge, Robin; Clyman, Stephen G.; Schwartz, Alan
Abstract : Purpose: To report on the development of content and user feedback regarding the assessment process and utility of the workplace-based assessment instruments of the Pediatrics Milestones Assessment Pilot (PMAP). Method: One multisource feedback instrument and two structured clinical observation instruments were developed and refined by experts in pediatrics and assessment to provide evidence for nine competencies based on the Pediatrics Milestones (PMs) and chosen to inform residency program faculty decisions about learners' readiness to serve as pediatric interns in the inpatient setting. During the 2012–2013 PMAP study, 18 U.S. pediatric residency programs enrolled interns and subinterns. Faculty, residents, nurses, and other observers used the instruments to assess learner performance through direct observation during a one-month rotation. At the end of the rotation, data were aggregated for each learner, milestone levels were assigned using a milestone classification form, and feedback was provided to learners. Learners and site leads were surveyed and/or interviewed about their experience as participants. Results: Across the sites, 2, 338 instruments assessing 239 learners were completed by 630 unique observers. Regarding end-of-rotation feedback, 93% of learners (128/137) agreed the assessments and feedback "helped me understand how those with whom I work perceive my performance, " and 85% (117/137) agreed they were "useful for constructing future goals or identifying a developmental path." Site leads identified several benefits and challenges to the assessment process. Conclusions: PM-based instruments used in workplace-based assessment provide a meaningful and acceptable approach to collecting evidence of learner competency development. Learners valued feedback provided by PM-based assessment.